A systematic review and meta-analysis of the effect of exercise on psychosocial outcomes in adults with obesity: A call for more research. (March 2018) - Baillot, Aurélie; Saunders, Stéphanie; Brunet, Jennifer; Romain, Ahmed J.; Trottier, Alexia; Bernard, Paquito
Abstract: Background: Reviews show that exercise reduces many obesity-related physical health problems. However, it is unclear whether those benefits extend to psychosocial outcomes. The aim of this review was to evaluate the effect of exercise on psychosocial outcomes in adults with obesity. Method: Seven databases (Pubmed, Cochrane Library, EMBASE, CINAHL, Psyarticle, SportDiscus, Proquest) were searched until October 2017 to identify relevant studies published in peer-reviewed journals. Two reviewers independently screened articles against the following inclusion criteria: used an experimental or quasi-experimental design, involved adults with a body mass index ≥30 kg/m 2, delivered an intervention consisting of supervised or semi-supervised exercise, and assessed quality of life (QoL), depression, anxiety, and/or body image as outcomes. Results: Twenty two articles were included in this review; 16 were randomized controlled trials (RCT). Most interventions were supervised and lasted ≤16 weeks. Meta-analysis of RCTs with available data on QoL (k = 7) and depression (k = 4) did not show that exercise was significantly superior to control conditions for physical QoL ( g  = 0.16, 95%CI [-0.05, 0.37]), mental QoL ( g  = 0.20, 95%CI [-0.09, 0.48]), or depression ( g  = −0.26, 95%CI [-0.70, 0.19]). Only three studies reported data on anxiety and body image. Conclusions: Current evidence does not suggest exercise is successful in significantly enhancing psychosocial health in adults with obesity. Limitations associated with the reviewed studies could have biased the results toward a lack of effect. Additional high-quality RCTs are needed to improve evidence-based knowledge. Highlights: Meta-analysis did not show that exercise was significantly superior to control conditions for quality of life or depression. In terms of anxiety and body image only three studies were found in adults with obesity. Additional trials are needed to know the effect of exercise on psychosocial functioning in adults with obesity.